Studi Literatur Kekurangan dan Kelebihan Pengujian Black Box - Rizky Parlika; Tasya Ardhian Nisaa’; Shavira Maya Ningrum; Berlianda Adha Haque (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2020)
A software cannot be perfect and always requires development. Software development consists of several stages, one of which is the testing stage. This stage aims to find fault with the software when doing software development. Stages of testing itself is divided into several techniques, one of which is black box testing. Black box testing is testing that only tests the outside of the software, for example, such as interface design. This is one of the reasons this test is appropriate to be used to test the software output. This paper is structured to look for the strengths and weaknesses of black box testing, content similarities, and differences in content by observing existing literature by the method of grouping these three things. Judging from some of the literature included in the observation, black box testing has many advantages and some drawbacks, some of the same contents, and several different contents.